2004
DOI: 10.1038/sj.emboj.7600092
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of photosynthetic membranes in Rhodobacter sphaeroides: the role of PufX

Abstract: The effects of the PufX polypeptide on membrane architecture were investigated by comparing the composition and structures of photosynthetic membranes from PufX þ and PufX À strains of Rhodobacter sphaeroides. We show that this single polypeptide profoundly affects membrane morphology, leading to highly elongated cells containing extended tubular membranes. Purified tubular membranes contain helical arrays composed solely of dimeric RC-LH1-PufX (RC, reaction centre; LH, light harvesting) complexes with apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
208
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(220 citation statements)
references
References 55 publications
10
208
2
Order By: Relevance
“…In this procedure, two bands ascribed to monomeric and dimeric states of the complex were observed. Recently, electron microscopy images similar to those obtained by Jungas et al (22) were reported for the same material (23) and in two-dimensional crystals reconstituted with purified RC⅐LH1 complexes (25). In the latter work, monomers were shown to dimerize upon reconstitution, supporting the view that the native structure in the membrane is dimeric.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In this procedure, two bands ascribed to monomeric and dimeric states of the complex were observed. Recently, electron microscopy images similar to those obtained by Jungas et al (22) were reported for the same material (23) and in two-dimensional crystals reconstituted with purified RC⅐LH1 complexes (25). In the latter work, monomers were shown to dimerize upon reconstitution, supporting the view that the native structure in the membrane is dimeric.…”
supporting
confidence: 73%
“…A small polypeptide, PufX, appears to play a key role in determining the structural organization. In its absence, the RC⅐LH1 complexes adopt a monomeric conformation with a closed LH1 ring of 16 ␣␤-heterodimers (23)(24)(25)27).…”
mentioning
confidence: 99%
“…Other modifications whose relation with the arrangement of RC⅐LH1 complexes is not straightforward are also observed. The structure of the intracytoplasmic membranes is affected (16,17), so membrane preparations do not yield sealed vesicles as in the WT. It may thus be hypothesized that the supramolecular arrangement of the RC⅐LH1 complexes affects the curvature of the membrane and controls in this manner its large-scale structure.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of a wide array of genetic tools for R. sphaeroides (16) can be exploited for AFM studies of membrane organization, because it allows control to be exerted over the composition of the proteins present in the membrane. Mutants of R. sphaeroides, which form highly ordered tubular membranes containing only RC-LH1-PufX dimers, have been used to study the organization of complexes by electron microscopy (17,18), and similar techniques have been applied to photosynthetic proteins reconstituted into two-dimensional crystals (19 -21). However, because the purification process removes the native lipids, and, in the case of R. sphaeroides, reconstitutes the complexes in an alternating, and therefore nonbiological, "up-down-up" topology, such work is unsuitable for examining the native organization of the complexes.…”
mentioning
confidence: 99%